The Effectiveness of Generative Learning in terms of Learning Independence of Students Problem Solving Abilities in the Phytagorean Theorem Material (Universitas Negeri Semarang, 2019)
This study aims to describe the generative learning of quality in in creasing problem solving abilities, to test the effect of learning independence on problem solving abilities, and to define problem solving abilities in terms of learning independence. This research method is mixed methods with concurrent triangulation model. The population of this research were VIII grade students of SMP Negeri 35 Semarang in 2018/2019 academic year, and samples were taken by cluster random sampling. The technique collection of data used such as a questionnaire of learning independence, a test of problem solving skills, documentation, observation, and interviews. The data analysis technique used the average similarity test, the proportion test, the average similarity test (two-sample t test), and simple linear regression. The results of this study indicate that students have good problem solving skills because of the enthusiasm in mathematics, understanding concepts, and feeling mastered the material. The study also showed that the generative learning model was declared effective, by indicators namely the problem solving ability of students reaching KKM (Minimum Mastery Criteria), the generative model produced problem solving abilities and students learning independence better than PBL (Problem Bae Learning), and the problem solving abilities of students to the generative model that affected their learning independence.